FEATURES OF GASTRIC AND DUODENAL ULCERS IN ELDERLY PATIENTS (World Bulletin of Public Health, 2022)
An increase in the number of elderly patients with peptic ulcer and its complications, an increase in the structure of the disease of ulcers of large and giant sizes, and long periods of scarring pose a serious problem in choosing a method of treating the disease
Keywords: endoscopy; gastric ulcer; duodenal ulcer; chronic gastritis